Knowledge and attitudes toward electroconvulsive therapy (ECT) among mental health workers and the public in Iceland - Díana Sif Ingadóttir 2000- (2023)
Electroconvulsive therapy (ECT) is commonly used to treat many major psychiatric disorders while being one of the most contentious procedures. Negative attitudes and misunderstandings about the procedure are prevalent, potentially due to the early use of ECT and the misrepresentations of the procedure in films. Previous studies suggest that greater knowledge of ECT correlates with positive attitudes toward ECT. The study aimed to examine the knowledge and attitudes toward ECT among mental health workers and the public in Iceland. A sample of 224 participants took part in the study by answering an online questionnaire. Results indicated that most participants had positive attitudes and adequate knowledge of ECT, but negative attitudes and misunderstandings about ECT were also present. Greater knowledge of ECT was correlated with more positive attitudes toward ECT. Mental health workers had greater knowledge and more positive attitudes toward ECT than the public. Knowledge of someone who has received ECT, or high education was not associated with more positive attitudes toward ECT. However, there was a correlation between greater knowledge of ECT and either knowledge of someone who has received ECT or high education. As no prior study has been conducted in Iceland, further research is needed to explore the knowledge and attitudes toward ECT in Iceland. Raflækningar er meðferð sem er notuð fyrir ýmsar geðraskanir, þó eru raflækningar ein umdeildasta meðferðin í geðlækningum. Neikvætt viðhorf og misskilningur um meðferðina má finna víða, hugsanlega vegna fyrrum notkunar á raflækningum og hvernig kvikmyndir hafa útfært meðferðina á rangan hátt. Fyrrum rannsóknir benda til þess að betri þekking á raflækningum tengist jákvæðu viðhorfi til meðferðarinnar. Markmið rannsóknarinnar var að kanna þekkingu og viðhorf til raflækningar meðal geðheilbrigðisstarfsmanna og almennings á Íslandi. Þátttakendur rannsóknarinnar voru 224 og svöruðu þeir rafrænum spurningalista. Niðurstöðurnar sýndu að flestir þátttakendur hefðu ...